1973
DOI: 10.2307/1165928
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Mothers and Their Young Children: Characteristics and Consequences

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
269
2
4

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(292 citation statements)
references
References 71 publications
17
269
2
4
Order By: Relevance
“…Many studies of cognitive development show that variation in input is related to achieved skill levels. First, children from homes providing more input do better on tests of ability and tests of achievement ( e g , A. W. Gottfried, 1984;Honig, 1982;Kellaghan, Sloane, Alvarez, & Bloom, 1993), and language development is significantly related to amount of vocal stimulation at home (e.g., Clarke-Stewart, 1973;Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1992;Snow & Ferguson, 1977). Second, children from schools providing more input attain higher skill levels than children from schools providing less input.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of cognitive development show that variation in input is related to achieved skill levels. First, children from homes providing more input do better on tests of ability and tests of achievement ( e g , A. W. Gottfried, 1984;Honig, 1982;Kellaghan, Sloane, Alvarez, & Bloom, 1993), and language development is significantly related to amount of vocal stimulation at home (e.g., Clarke-Stewart, 1973;Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1992;Snow & Ferguson, 1977). Second, children from schools providing more input attain higher skill levels than children from schools providing less input.…”
Section: Introductionmentioning
confidence: 99%
“…L'analyse de ces interactions indique que les parents des bébés présentant des difficultés développe-mentales se comportent différemment des parents des bébés qui se déve-loppent de façon optimale (Bradley et Caldwell, 1980;Clarke-Stewart, 1973). Les mères de familles vulnérables utilisent un style moins didactique et centré sur la tâche ou les objets que le font les mères d'autres milieux, n'incitant pas ainsi l'enfant à explorer ou à porter attention à son environnement (Tamis-LeMonda et Bornstein, 1993).…”
Section: Importance De L'interaction Parent-nourrisson Dans Ie Dévelounclassified
“…9, 1971). This method is preferable to others for collecting behavioral data because the latter may be affected by selective recall and distortion on the part of the subject, certain difficulties with discrimination and synthesis for the re searcher, and a lack of sensitivity to behavioral dynamics of inter action (Clarke-Stewart, 1973). Weiss (1972b) suggested that many evaluators rely mostly on attitudinal and cognitive measures, avoiding the more difficult be havioral data.…”
Section: Observationmentioning
confidence: 99%
“…The rating scales used five-point continua. Elardo, Bradley, and Caldwell (1975) The study by Clarke-Stewart (1973), which was discussed ear lier, also used in interview schedule to collect data. In examin ing the relations between mothers and their children, the investiga tor used a maternal attitude score based on the number of "yes"…”
Section: Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation